2023
DOI: 10.1038/s41598-023-27410-z
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear EHD instability of two viscoelastic fluids under the influence of mass and heat transfer

Abstract: This study attempts to provide an approach to studying the nonlinear stability of a vertical cylindrical interface between two Oldroyd-B prototypes. An unchanged axial electric field influences the system, and porous medium, and the effects of heat and mass transfer (MHT) are considered. Hsieh's modulation and the viscous potential flow (VPT) are used to abbreviate the mathematical analysis. The viscoelastic Oldroyd-B model significant role in geothermal, engineering and industrial enhancement motivated us to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Authors have concluded that the system is stable for certain values of the parameters, while it becomes unstable for others. The study provides insights into the behavior of the system and its potential applications in various fields 41,42 …”
Section: Introductionmentioning
confidence: 99%
“…Authors have concluded that the system is stable for certain values of the parameters, while it becomes unstable for others. The study provides insights into the behavior of the system and its potential applications in various fields 41,42 …”
Section: Introductionmentioning
confidence: 99%
“…Cham and Mustafa [11], Behbahan et al [12], Moatimid et al [13] and Marinca et al [14]. Viscoelastic models had also been utilized by researchers to investigate other interesting flow scenarios, such as channel flows [15], flow in a rectangular duct [16], peristaltic flows [17][18][19] and rotating-disk produced flows [20][21][22], just to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Some related works about different numerical algorithms of such models were given 3 . The nonlinear stability of a vertical cylindrical interface between two Oldroyd-B prototypes was studied 4 . The current investigation is developed in the cooperation with the viscoelastic Oldroyd-B flow because of its importance in numerous areas.…”
Section: Introductionmentioning
confidence: 99%